Service Promotion Strategies in the Digital Economy Era: Leveraging Technology and Electronic Communications to Face Challenges and Seize Opportunities - Sinarwaty Sinarwaty; Rachmiani Rachmiani (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
This research will analyze the service sector that distributes services through technology and electronic communication in the digital economy era. This research was conducted using descriptive qualitative methods, supplemented by basic quantitative data. Data collection was carried out through a literature review and interviews with service business actors who place orders through digital media (social networks, websites, mobile applications, and related online stores). The results of the study indicate that digital technology has marketing diversification, consumer engagement, and promotional efficiency. Social media is developing as the strongest source of consumer attention, leading to needs triggered by purchases and therefore the need for applications such as e-commerce and mobile applications for transaction/service access. Higher technology adoption leads to increased sales, customer loyalty, and better business growth. The successful implementation of promotional activities is also hampered by human resources (availability, digital literacy), and the speed of adaptation to technological developments. Improved competence and appropriate technology management are needed to increase the competitiveness of service businesses.